2021
DOI: 10.1186/s40623-020-01352-6
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous alteration without initial water: possibility of organic-induced hydration of anhydrous silicates in meteorite parent bodies

Abstract: Early evolution of Solar System small bodies proceeded through interactions of mineral and water. Melting of water ice accreted with mineral particles to the parent body results in the formation of secondary minerals, the so-called aqueous alteration. Formation of phyllosilicates from anhydrous silicates is a typical alteration effect recorded in primitive meteorites. In addition to mineral and water, organic matter could have been also a significant component in meteorite parent bodies. However, the role of o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 68 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…This dependence may indicate a possible role played by the phyllosilicates in the protection and/or formation of organic matter in hydrated IDPs. It could also indicate the role of organic matter on phyllosilicate formation as reported by Hirakawa et al (2021). This process occurs on dry meteorites such as meteorites of the CO and CV groups and is therefore associated with significant graphitization of organic matter (e.g., Nakamura 2005;Hirakawa et al 2021).…”
Section: Organic Matter and Silicate Compositionmentioning
confidence: 76%
See 1 more Smart Citation
“…This dependence may indicate a possible role played by the phyllosilicates in the protection and/or formation of organic matter in hydrated IDPs. It could also indicate the role of organic matter on phyllosilicate formation as reported by Hirakawa et al (2021). This process occurs on dry meteorites such as meteorites of the CO and CV groups and is therefore associated with significant graphitization of organic matter (e.g., Nakamura 2005;Hirakawa et al 2021).…”
Section: Organic Matter and Silicate Compositionmentioning
confidence: 76%
“…The hydration process on CM-type meteorites comes from the melting of the ice contained in the parent body by the heating induced by radioactive decay of the elements with short periods (e.g., Brearley 2006;Merk & Prialnik 2006 and references therein). Liquid water circulation on parent bodies causes the alteration of minerals (hydration) and leads to redistribution and migration of elements (Brearley 2006;King et al 2017;Hirakawa et al 2021). Yesiltas & Kebukawa (2016) also showed a correlation between organic matter and phyllosilicates in grains of the Tagish Lake meteorite (based on the OH band at 3050 cm −1 ) and concluded that phyllosilicates can play a role in the formation and/or protection of organic matter in the parent body.…”
Section: Organic Matter and Silicate Compositionmentioning
confidence: 99%
“…They demonstrate that when evidence of alteration exists, it is predominantly isochemical at the scale of the chondrules and matrix, likely confined to zones within 100-200 µm around anhydrous chondrules. Moreover, Hirakawa et al [52] proved that organic mat- A schematic illustration of the three modes of water rock interaction in asteroid (modified after [49]). The diagram illustrates porosity at a macroscopic scale (in kilometers), while the calculations are conducted using microscopic (grain-scale) porosity for accuracy [49].…”
Section: Aqueous Alteration In Meteoritesmentioning
confidence: 99%
“…They demonstrate that when evidence of alteration exists, it is predominantly isochemical at the scale of the chondrules and matrix, likely confined to zones within 100-200 µm around anhydrous chondrules. Moreover, Hirakawa et al [52] proved that organic matter-mineral interaction could also lead to in-situ aqueous alteration through water generation by decomposition of organic compounds with hydroxy groups after heating. In this case, it forms locally hydrated phyllosilicates on the surface of olivine in carbonaceous chondrites.…”
Section: Aqueous Alteration In Meteoritesmentioning
confidence: 99%
“…At similar temperatures, but in an open system where fluids are flowing through the rock and altering the composition, is referred to as metasomatism [336]. Some recent experimental studies have suggested that the initial parent body composition need not contain water, as heat from impact [337] or organic degradation [338] could induce aqueous alteration on parent bodies.…”
Section: Compositional Alteration On Other Planetary Bmentioning
confidence: 99%